Entry-level accounting positions competencies in the UAE: perceptions of accounting educators and financial managers. (22nd February 2010) - Shahwan, Yousef; Roudaki, Jamal
In recent years, increasing attention has been given to the knowledge, practices and theories required from accounting graduates for performing accounting-related jobs. The main purpose of this study was to determine competencies needed by accounting graduates of the UAE universities. The primary sources for this research were accounting educators and financial managers, who responded to a questionnaire survey about competencies needed by entry-level accountants. Descriptive statistic was used to analyse collected data. The results indicated that all competencies which have been recommended by IFAC are considered important by the UAE accounting educators and financial managers to be included in the university accounting program.